Analysis of the variations in price of anti-glaucoma eye preparations available in Indian pharmaceutical market - Kumar, Sonu; Chandra, Anupam; Chandra, Akash Prasad; Kesari, Uma Shankar Prasad (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The aim of the study was to analyze the percentage cost variations among different brands of the commonly prescribed anti–glaucoma drugs. Methods: The maximum and minimum price of each brand of the drug in INR was noted by using CIMS January to April 2018 edition Drug Today April to June 2018 Vol-1. The cost ratio and the percentage cost variation for individual drug brands was calculated. The cost of each eye drop was calculated. At last the cost ratio and percentage cost variation of various brands was compared. Results: Percentage variation in cost for anti-glaucoma eye preparations marketed in india was found to be eye drop timolol maleate (0.5%) of 5 ml:263.63, eye drop dorzolamide (2%) of 5 ml:9.77, eye drop pilocarpine (2%) of 5 ml:160.40, eye drop Betaxolol (0.5%) of 5 ml:56.54, eye drop Latanoprost (50 mcg/ml) of 2.5ml:135.88, eye drop Brimonidine tartarate (0.15%) of 5 ml:183.9, eye drop Levobunolol (5 mg/ml) of 5 ml:32.38. Conclusions: Glaucoma is the most common ocular disease and eye drops are to be prescribed for prolonged period. If a costly brand is prescribed, the patients have to pay more money unnecessarily for their treatment. The clinicians prescribing these drugs should be aware of these variations in cost to reduce the cost of drug therapy.